Climate change and nesting behaviour in vertebrates: a review of the ecological threats and potential for adaptive responses - Mainwaring, Mark C.; Barber, Iain; Deeming, Denis C.; Pike, David A.; Roznik, Elizabeth A.; Hartley, Ian R. (Biological reviews of the Cambridge Philosophical Society, 2017)
ABSTRACT Nest building is a taxonomically widespread and diverse trait that allows animals to alter local environments to create optimal conditions for offspring development. However, there is growing evidence that climate change is adversely affecting nest‐building in animals directly, for example via sea‐level rises that flood nests, reduced availability of building materials, and suboptimal sex allocation in species exhibiting temperature‐dependent sex determination. Climate change is also affecting nesting species indirectly, via range shifts into suboptimal nesting areas, reduced quality of nest‐building environments, and changes in interactions with nest predators and parasites. The ability of animals to adapt to sustained and rapid environmental change is crucial for the long‐term persistence of many species. Many animals are known to be capable of adjusting nesting behaviour adaptively across environmental gradients and in line with seasonal changes, and this existing plasticity potentially facilitates adaptation to anthropogenic climate change. However, whilst alterations in nesting phenology, site selection and design may facilitate short‐term adaptations, the ability of nest‐building animals to adapt over longer timescales is likely to be influenced by the heritable basis of such behaviour. We urgently need to understand how the behaviour and ecology of nest‐building in animals is affected by climate change, and particularly how altered patterns of nesting behaviour affect individual fitness and population persistence. We begin our review by summarising how predictable variation in environmental conditions influences nest‐building animals, before highlighting the ecological threats facing nest‐building animals experiencing anthropogenic climate change and examining the potential for changes in nest location and/or design to provide adaptive short‐ and long‐term responses to changing environmental conditions. We end by identifying areas that we believe warrant the most urgent attention for further research.